2019
DOI: 10.18671/scifor.v47n124.15
|View full text |Cite
|
Sign up to set email alerts
|

Temperatura e radiação solar na produção de mudas de cedro australiano

Abstract: O objetivo do trabalho foi estimar a temperatura base para emissão de folhas e determinar a eficiência do uso da radiação na produção de mudas de cedro australiano. Foram utilizadas duas densidades de mudas na bandeja, 100 e 50%, denominados densidade alta e média, sendo que a densidade alta apresentava 494 plantas m-2 e a média, 247 plantas m-2. Avaliou-se a temperatura base para emissão de folhas, filocrono, índice de área foliar, fitomassa seca total acumulada, coeficiente de extinção luminosa e eficiência … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…There was no clear trend in relation to the season, since higher means were observed in both autumn and spring for the different characteristics (Table 3), showing that the sowing time was not a factor that influenced the production of T. stans seedlings. However, it should be noted that plants change their morphology according to soil and climatic conditions, and as there is an increase in solar radiation, the greater the rate of emission and expansion of leaves and, consequently, the greater the leaf area index, increasing the leaf efficiency in converting photosynthetically active radiation into phytomass (Schwerz et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…There was no clear trend in relation to the season, since higher means were observed in both autumn and spring for the different characteristics (Table 3), showing that the sowing time was not a factor that influenced the production of T. stans seedlings. However, it should be noted that plants change their morphology according to soil and climatic conditions, and as there is an increase in solar radiation, the greater the rate of emission and expansion of leaves and, consequently, the greater the leaf area index, increasing the leaf efficiency in converting photosynthetically active radiation into phytomass (Schwerz et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The estimate of IPAR was determined using the model described by Varlet-Grancher et al (1989). The extinction coefficients used for the study were those found 3 -11 by Schwerz et al (2019): values of 0.18 and 0.13 for high and medium densities, respectively.…”
Section: Radiation Use Efficiency and Leaf Area Indexmentioning
confidence: 99%